1992
DOI: 10.1099/00221287-138-4-803
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of pyruvate decarboxylase from Sarcina ventriculi

Abstract: Pyruvate decarboxylase from the obligate anaerobe Sarcina ventricufi was purified eightfold. The subunit M, was 57000 3OOO as estimated from SDS-PAGE, and the native M, estimated by gel filtration on a Superose 6 column was 240000, indicating that the enzyme is a tetramer. The M, values are comparable to those for pyruvate decarboxylase from Zymomonas mobifis and Saccharomyces cereoisiue, which are also tetrameric enzymes. The enzyme was oxygen stable, and had a pH optimum within the range 6.3-6.7. It displaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 21 publications
(13 reference statements)
5
25
0
Order By: Relevance
“…Previous studies have demonstrated that the PDC purified from S. ventriculi also retains the N-terminal methionine which is amino to a lysine residue (28,45). In contrast, the N-terminal sequence of PDC purified from A. pasteurianus (TYTVGMYLAERL) lacked an N-terminal methionine, suggesting cleavage by a native methionine aminopeptidase.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Previous studies have demonstrated that the PDC purified from S. ventriculi also retains the N-terminal methionine which is amino to a lysine residue (28,45). In contrast, the N-terminal sequence of PDC purified from A. pasteurianus (TYTVGMYLAERL) lacked an N-terminal methionine, suggesting cleavage by a native methionine aminopeptidase.…”
Section: Resultsmentioning
confidence: 83%
“…In contrast, PDC is common to only plants, yeasts, and fungi; it is absent in animals and rare in prokaryotes (25). PDC has been established by cloning and purification for only three bacteria, Zymomonas mobilis (6,7,11,19,33,34), Sarcina ventriculi (28,45), and Acetobacter pasteurianus (40). Though cloned from plants and fungi (25,38), only bacterial PDC enzymes are produced at high levels as active recombinant products (6,10,11,34,40,45).…”
mentioning
confidence: 99%
“…Alternatively, a pdc gene with optimized codon usage could be synthesized for high-level production of alternative PDCs. SvPDC has qualities that make it unique among bacterial PDCs, including its substrate activation and elevated pH optimum (Lowe & Zeikus, 1992;Talarico et al, 2001). However, in comparison to other PDCs, the K M of SvPDC for pyruvate is over tenfold higher (Raj et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, only low levels of the ZmPDC, ApPDC and ScPDC1 proteins were detected. To determine if the PDC proteins were produced in an active form, the cell lysate of the recombinant B. megaterium strains was assayed for PDC activity ( (Lowe & Zeikus, 1992;Talarico et al, 2001). The results demonstrate that SvPDC is not only produced in very high quantity, but is produced in an active form within the B. megaterium host cell.…”
Section: Expression Of Pdc In Recombinant B Megateriummentioning
confidence: 99%
“…It has been demonstrated that the position and usage frequency of codons, together, play a role in correct protein folding and that "codon harmonization" could be used to overcome poor expression, at least in E. coli (Angov et al, 2008;Rosano et al, 2009). Incompatibilities in codon usage and their effect on expression of PDCs have been reported (Lowe et al, 1992;Talarico et al, 2001;Talarico et al, 2005). Two examples of the effect of codon usage on PDC production include the 5-10 fold increase in soluble SvePDC when expressed in an E. coli strain with or without accessory tRNAs (specifically those which are rarely used in E. coli), as well as the superior production of this PDC relative to those from A. pasteurianus and Z. mobilis in B. megatarium (Talarico et al, 2001;Raj et al, 2002;Talarico et al, 2005).…”
Section: Introductionmentioning
confidence: 99%